Relationship between C-Reactive Protein and Cardiovascular Diseases in Patient with ESRD - Al Mamun, Md Abdullah; Hasan, Mohammad Mirazul; Khan, Fazla Alahi; Hossain, Momtaz; Morshed, Syed Mahbub; Gupta, Ratan Das (Journal of Shaheed Suhrawardy Medical College, 2022)
Background- Cardiovascular mortality is significantly higher in ESRD patient.There are various risk factors for development of cardiovascular diseases including traditional risk factors, factors unique to ESRD patients and emerging risk factors.It is believed that their combined actions are integrated in the progression of atherosclerosis and inflammation plays a central role. C-reactive protein is a valuable marker of inflammation. Determination of serum creactive protein levels may be a useful predictor of cardiovascular diseases in ESRD patients Objective-To find out relationship between c-reactive protein and cardiovascular diseases. Methods- This cross sectional study was carried out into department of Nephrology, Dhaka Medical College Hospital, Bangladesh following fulfillment of inclusion and exclusion criteria. For analytical purpose total study population were divided into two groups on the basis of creactive protein level. Patients having c-reactive protein £6 mg/L were considered as group A and >6 mg/L were considered as Group B. The differences between groups were analyzed by unpaired t-test, fisher’ exact test or chi-square (X2) test. Multivariable regression analysis was done to see the association between c-reactive protein and cardiovascular diseases. Results- Patients with raise c-reactive protein have significantly higher cardiovascular disease than that of normal c-reactive protein. Multivariable linear regression analysis after adjusting for age, sex, smoking and diabetes shows that subject with CRP £6 mg/L vs >6 mg/L had 1.51 (95% CI 1.02 to 2.19) times increase risk of having cardiovascular disease. Conclusion- Inflammatory process has a role in development of cardiovascular diseases in ESRD patient. J Shaheed Suhrawardy Med Coll 2020; 12(2): 95-99